Validation of an automated immune turbidimetric assay for serum gelsolin and its possible clinical utility in sepsis. Issue 3 (5th September 2017) - Horváth‐Szalai, Zoltán; Kustán, Péter; Szirmay, Balázs; Lakatos, Ágnes; Christensen, Per H.; Huber, Tamás; Bugyi, Beáta; Mühl, Diána; Ludány, Andrea; Miseta, Attila; Kovács, Gábor L.; Kőszegi, Tamás
Abstract : Background: Studies showing the potential predictive value of the actin‐binding protein gelsolin, in critically ill patients are scarce. Moreover, even up to now a rapid automated measurement of gelsolin has still remained a challenge. Therefore, we developed and validated an automated serum gelsolin immune turbidimetric assay for possible clinical use. Methods: Validation of serum gelsolin assay was performed on a Cobas 8000/c502 analyzer (Roche) according to the second edition of Eurachem guidelines. Furthermore, we also studied the diagnostic value of serum gelsolin in sepsis when investigating sera of septic (n = 25), systemic inflammatory response syndrome (SIRS; n = 8) and control patients (n = 14). We compared our previously published Western blot data with those of the new turbidimetric assay. Results: The sample volume was 7 μL and the assay time was 10 minutes. The detection limit was 0.72 mg/L, intra‐ and inter‐assay imprecision remained in most cases less than 5% expressed as CV. Recovery was found to be 84.56%‐93.52% and linearity study gave an appropriate correlation coefficient by linear regression analysis ( r 2  = .998). Septic patients exhibited lower ( P  = .015) first‐day serum gelsolin levels than SIRS patients, which confirmed our previous Western blot results. The determined cut‐off point for serum gelsolin was 14.05 mg/L (sensitivity: 75%; specificity: 60%) when investigating its diagnostic value in sepsis. Conclusion: Based on the results, our immune turbidimetric measurement offers a rapid and accurate quantitation of gelsolin in human serum samples. Serum gelsolin seems a promising additional diagnostic marker of sepsis which has to be further investigated.